Conscious sedation versus general anesthesia in transcatheter aortic valve replacement: the German aortic valve registry - Husser, Oliver; Fujita, Buntaro; Bekeredjian, Raffi (JACC Cardiovascular interventions, 2018)
Objectives - The aims of this study were to report on the use of local anesthesia or conscious sedation (LACS) and general anesthesia in transcatheter aortic valve replacement and to analyze the impact on outcome. - Background - Transcatheter aortic valve replacement can be performed in LACS or general anesthesia. Potential benefits of LACS, such as faster procedures and shorter hospital stays, need to be balanced with safety. - Methods - A total of 16,543 patients from the German Aortic Valve Registry from 2011 to 2014 were analyzed, and propensity-matched analyses were performed to correct for potential selection bias. - Results - LACS was used in 49% of patients (8,121 of 16,543). In hospital, LACS was associated with lower rates of low-output syndrome, respiratory failure, delirium, cardiopulmonary resuscitation, and death. There was no difference in paravalvular leakage (II+) between LACS and general anesthesia in the entire population (5% vs. 4.8%; p = 0.76) or in the matched population (3.9% vs. 4.9%, p = 0.13). The risk for prolonged intensive care unit stay (≥3 days) was significantly reduced with LACS (odds ratio: 0.82; 95% confidence interval [CI]: 0.73 to 0.92; p = 0.001). Thirty-day mortality was lower with LACS in the entire population (3.5% vs. 4.9%; hazard ratio [HR]: 0.72; 95% CI: 0.60 to 0.86; p < 0.001) and in the matched population (2.8% vs. 4.6%; HR: 0.6; 95% CI: 0.45 to 0.8; p < 0.001). However, no differences in 1-year mortality between both groups in the entire population (16.5% vs. 16.9%; HR: 0.93; 95% CI: 0.85 to 1.02; p = 0.140) and in the propensity-matched population (14.1% vs. 15.5%; HR: 0.90; 95% CI: 0.78 to 1.03; p = 0.130) were observed. - Conclusions - Use of LACS in transcatheter aortic valve replacement is safe, with fewer post-procedural complications and lower early mortality, suggesting its broad application.
Gesehen am 22.01.2020